Antiepileptic Drugs and the Relationship with the Intestinal Microbiota (Global Journal of Medical Research, 2024)
This review of the literature examines the use of antiepileptic medications and how they relate to gut microbiota. Relationships exist between the makeup of the intestinal microbiota and the development and execution of the most fundamental physiological processes. Additionally, it affects the functioning of the central nervous system (CNS) by interacting with the microbiota-intestine-brain axis. The use of pharmaceutical medication is one of the factors that can alter the composition of the gut microbiota. When treating epilepsy, various drug types are used, each with a different mechanism of action. Among the medications in question are topiramate, primidone, phenytoin, carbamazepine, and phenobarbital. The similarity in structure and function between enteric and nerve cells establishes the connection between the brain and the gut.